Promoting dry direct seeding of rice in line with post-emergence application of herbicide for higher productivity - Jain, Vinamarta; Rajak, Krishnakant; Singh, S R K (Indian Farming, 2022)
Under Farmer FIRST Programme, scientists successfully initiated dry direct seeded rice with effective weed management at farmers’ field of 5 adopted villages in tribal area of Chhattisgarh with improved paddy variety and seed-cum-fertilizer drill. The demonstrations were conducted on line sowing with the use of post-emergence herbicide in rice in 65 ha area. The study revealed that the higher grain yield of rice could be achieved with application of bispyribac sodium applied at 20 DAS at the rate of 200 ml/ha or 200 g/ha. The net monetary return and benefit cost (B: C) ratio were higher in improved demonstrated technology. It is concluded from the trail that the line sowing of rice with application of post-emergence herbicides gave higher yield and net monetary return at farmers’ field of Ambagarh Chowki block of Chhattisgarh plain.